2014
DOI: 10.1063/1.4891333
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength excitation Raman scattering of Cu2ZnSn(SxSe1−x)4 (0 ≤ x ≤ 1) polycrystalline thin films: Vibrational properties of sulfoselenide solid solutions

Abstract: In this work, Raman spectroscopy and X-ray diffraction were applied together to evaluate the crystal structure and the phonon modes of photovoltaic grade Cu2ZnSn(SxSe1−x)4 thin films, leading to a complete characterization of their structural and vibrational properties. Vibrational characterization has been based on Raman scattering measurements performed with different excitation wavelengths and polarization configurations. Analysis of the experimental spectra has permitted identification of 19 peaks, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 24 publications
12
53
0
Order By: Relevance
“…Fig. 3 shows Raman spectra of sample A and sample B where the presence of the same peak at 197-202 cm −1 could be assigned to the A mode of Cu 2 ZnSnSe 4 kesterite [17], whereas the peak at 329 cm −1 was assigned to Cu 2 ZnSnS 4 [20]. This is in good agreement with the bimodal behavior of the CZTSSe alloy already observed by Grossberg et al [21].…”
Section: Ramansupporting
confidence: 78%
See 1 more Smart Citation
“…Fig. 3 shows Raman spectra of sample A and sample B where the presence of the same peak at 197-202 cm −1 could be assigned to the A mode of Cu 2 ZnSnSe 4 kesterite [17], whereas the peak at 329 cm −1 was assigned to Cu 2 ZnSnS 4 [20]. This is in good agreement with the bimodal behavior of the CZTSSe alloy already observed by Grossberg et al [21].…”
Section: Ramansupporting
confidence: 78%
“…This two-zone CZTSSe has already been observed in literature for vacuum deposited absorber [14][15]: Zone 1 is typically identified as a CZTSSe layer with big grains and low residual carbon content, while Zone 2 is instead pinpointed as a small crystals CZTSSe layer with high residual carbon content, as demonstrated in other non-vacuum CZTSSe deposition technologies [15][16][17] and in this work by EDX analysis (not shown here). In Fig.…”
Section: Semsupporting
confidence: 55%
“…However, since the absorber composition was slightly Ge-poor, it is more likely that it was one more sulfoselenide mode related to vibrations of both S and Se anions. A similar behavior has been reported for CZTSSe by Dimitrievska et al, who observed three additional sulfoselenide modes in addition to the CZTS-like and CZTSe-like modes [19].…”
Section: The [S]/([s] + [Se]supporting
confidence: 62%
“…However, detection of part of these minor phases is not straightforward: due to signal overlapping, simple X-Ray Diffraction (XRD) cannot be used 82 . More sophisticated methods need thus to be employed, such as multi-wavelength Raman spectroscopy 84 , X-ray absorption near edge structure analyses (XANES) 83 , scanning transmission electron microscopy (STEM) in combination with energy dispersive X-ray spectroscopy 85 or atom probe tomography 66 .…”
Section: Occurrence Quantification In Literaturementioning
confidence: 99%